Mass Spectrometric Analysis of Antibody—Epitope Peptide Complex Dissociation: Theoretical Concept and Practical Procedure of Binding Strength Characterization - Bright D. Danquah; Kwabena F. M. Opuni; Claudia Roewer; Cornelia Koy; Michael O. Glocker (Molecules, 2020)
Electrospray mass spectrometry is applied to determine apparent binding energies and quasi equilibrium dissociation constants of immune complex dissociation reactions in the gas phase. Myoglobin, a natural protein-ligand complex, has been used to develop the procedure which starts from determining mean charge states and normalized and averaged ion intensities. The apparent dissociation constant <semantics><msubsup>KD m0g#</msubsup>=</semantics> 3.60 × 10−12 for the gas phase heme dissociation process was calculated from the mass spectrometry data and by subsequent extrapolation to room temperature to mimic collision conditions for neutral and resting myoglobin. Similarly, for RNAse S dissociation at room temperature a <semantics><msubsup>KD m0g#</msubsup>=</semantics> 4.03 × 10−12 was determined. The protocol was tested with two immune complexes consisting of epitope peptides and monoclonal antibodies. For the epitope peptide dissociation reaction of the FLAG peptide from the antiFLAG antibody complex an apparent gas phase dissociation constant <semantics><msubsup>KD m0g#</msubsup>=</semantics> 4.04 × 10−12 was calculated. Likewise, an apparent <semantics><msubsup>KD m0g#</msubsup>=</semantics> 4.58 × 10−12 was calculated for the troponin I epitope peptide—antiTroponin I antibody immune complex dissociation. Electrospray mass spectrometry is a rapid method, which requires small sample amounts for either identification of protein-bound ligands or for determination of the apparent gas phase protein-ligand complex binding strengths.